Introduction to drone technology for agriculture purposes: a brief review - Saiful Iskandar, Khalit; Noor Afiza, Badaluddin; Noor Atiqah, Badaluddin (2020)
Decades ago, drones developed for the uses of the military as they without a human pilot and can save more lives during war and battlefield. With the technology transformations in this recent year, drones are expanding their application to other areas such as photography, environment, and agriculture. Special features and facilities fitted to the drone such as HD cameras, GPS, tracker, smart sensors and others to enhance the drone’s functions. As for agriculture, companies and fellow researchers uncover the drone technology and developing it for agriculture purposes to overcome challenges faced by the farmers to produce better crop yields. Drones are one of the excellent approaches to improve the crop by aerial monitoring, analyzing and spraying. The technology of drones and its purposes for agriculture that was uncovered by fellow researchers will be compiled and reviewed on this paper hoping that it could bring advantages, especially to farmers to ease their difficulties.